The big seven a faux mystery - Harrison, Jim 1937-2016 (Grove Press, 2015)
The Big Seven sends Detective Sunderson to confront his new neighbors, a gun-nut family who live outside the law in rural Michigan. Detective Sunderson has fled troubles on the home front and bought himself a hunting cabin in a remote area of Michigan's Upper Peninsula. No sooner has he settled in than he realizes his new neighbors are creating even more havoc than the Great Leader did. A family of outlaws, armed to the teeth, the Ameses have local law enforcement too intimidated to take them on. Then Sunderson's cleaning lady, a comely young Ames woman, is murdered, and black sheep brother Lemuel Ames seeks Sunderson's advice on a crime novel he's writing which may not be fiction. Sunderson must struggle with the evil within himself and the far greater, more expansive evil of his neighbor